ISLAM HUMANIS, HAM, DAN HUMANISASI PENDIDIKAN: Eksposisi Integratif Prinsip Dasar Islam, Kebebasan Beragama, Kesetaraan Gender, dan Pendidikan Humanis - Arif, Mahmud (Sunan Kalijaga State Islamic University & The Asia Foundation, 2016)
The issue of human rights has prevailed globally although it is can’t denied that historically that issue comes from tradition of the West Liberalism based on individualism standpoint. In fact, freedom and equality as essential part of human rights have not been appreciated yet suitably in the realm of long history of humankind so it was still found the slavery system. Even in the modern time, at several regions, the right of vote consisting of human right has not possessed by the women. There was a accusation from some scholars in the West that Islam is a religion opposing to human rights and gender equality. They argue that Islam has justified any religious violence, has cut religious freedom down, and has tolerated gender unequality. If it is viewed from the basic principle of takhfif wa rahmah (giving easiness and love), such accusation looks obviously problematic, because Islamic tenets normatively appreciate to establish human rights and gender equality. But empirically, religious interpretation often contributes in mainstreaming culture that castrates any religious freedom and gender equality. As one of religious interpretation product, fiqih (Islamic jurisprudence) for instance is claimed to contain many problems relating to religious freedom and gender equality. Such is the case, the reality of our national education. For a long time, in the Indonesian school system there are many factors causing failure of every endeavor for achieving the aim of human right education. This means that such basic priciple must be reactualized in the education system through hard efforts in humanizing education processes and pupil’s potencies.[Isu hak asasi manusia (HAM) telah mencuat sedemikian universal meski tidak bisa dinafikan bahwa dalam sejarahnya isu ini bermula dari tradisi liberalisme Barat yang titik pijaknya individual. Kebebasan dan kesetaraan sebagai elemen penting HAM ternyata belum diapresiasi secara semestinya dalam sejarah panjang pelbagai peradaban sehingga masih ditemukan adanya sistem perbudakan. Bahkan dalam kurun modern ini pun di sebagian wilayah, hak untuk memilih yang menjadi bagian dari hak asasi belum juga dinikmati oleh kaum perempuan. Muncul tuduhan dari sebagian kalangan di Barat bahwa Islam adalah agama anti HAM dan bias gender. Argumen yang dikemukakan, Islam membenarkan tindak kekerasan atasnama agama, memasung kekebasan beragama, dan mentolerir ketidakadilan terhadap perempuan. Diletakkan dalam konteks prinsip dasar takhfif wa raḥmah, tuduhan tersebut nampak problematik, mengingat secara normatif ajaran Islam sangatlah menjunjung tinggi penegakan HAM dan kesetaraan gender. Hanya saja, dalam realitas empirisnya tafsir keagamaan tidak jarang justru ikut andil dalam pembentukan arus besar budaya yang memberangus kebebasan beragama dan ketidakadilan terhadap kaum perempuan. Sebagai salah satu produk tafsir keagamaan, fikih misalnya diakui masih menyimpan banyak persoalan menyangkut kekebasan beragama dan kesetaraan gender. Demikian halnya dengan dunia pendidikan nasional. Selama ini, dalam sistem persekolahan di Indonesia masih banyak ditemukan faktor penyebab kegagalan bagi setiap upaya mencapai tujuan pendidikan HAM. Ini berarti prinsip dasar tersebut perlu diejawantahkan dalam sistem pendidikan melalui upaya memaksimalkan peran humanisasi dan hominisasi pendidikan.]